Effect of Ephemeral Content on Compulsive Buying : FoMO and Impulsivity Roles - R., Dharshini; Santhi, P. (Indian Journal of Marketing, 2025)
Purpose : In the social marketing era, marketers use various strategies to connect with customers. One such strategy is ephemeral content, which allows marketers to create a sense of urgency among customers and drive immediate engagement. This strategy has also brought several challenges to customers, such as online compulsive buying (OCB). This research sought to determine the effect of ephemeral content on OCB, with FoMO as a mediator and impulsivity as the moderator among female shoppers. Design/Methodology/Approach : An online survey targeting female customers who purchased through social media was conducted. The study used a sample of 253 respondents and focused on ephemeral content, FoMO, impulsivity, and OCB. The data was collected from May to June 2024, and the ethical procedures followed the rules outlined by the Institutional Human Ethical Committee. Findings : The results exhibited a significant relationship between ephemeral content and OCB, and FoMO partially mediated this relationship. Moreover, impulsivity moderated both the links between ephemeral content and OCB and the mediating role of FoMO in women with high impulsivity. These findings proved that women’s OCB habits were complex. Practical Implications : Marketers could create more tailored promotional strategies, considering the well-being of consumers. Moreover, as FoMO and impulsivity are major factors in influencing OCB, focused interventions to reduce OCB among women can be concentrated. Originality : The present study focused on the ephemeral content’s temporally confined nature, which is frequently used in social media marketing. By analyzing how ephemeral content is associated with FoMO and impulsivity, it offers the mechanisms for tailoring the advertising strategies impacting OCB. This will have effective interventions in understanding OCB among women.